Jambu Flower Extract (Acmella oleracea) Increases the Antioxidant Potential of Beer with a Reduced Alcohol Content - Suelem Paixão da Silva; José Augusto Lacerda Fernandes; Alberdan Silva Santos; Nelson Rosa Ferreira (Plants, 2023)
Craft beers with different sensory perceptions have received the attention of more demanding consumers. In this sense, the application of plant extracts as brewing adjuncts is being increasingly studied. Allied with these perspectives is the consumption of lower alcoholic beverages, which also represents the desire for a market niche that has been growing gradually. The present work aimed to produce craft lager beer with the addition of plant extract and reduced alcohol content by partial replacement of malt with malt bagasse. The physical-chemical analyzes of the beer produced showed that it was possible to reduce the alcohol content by 40.5% compared to the control sample. In addition, an extract of Acmella oleracea (Jambu) obtained by supercritical extraction was added to increase the beer’s antioxidant capacity. The ABTS, DPPH, and ORAC methods evaluated the antioxidant capacity. These assays were performed again after six months of storage. The quantification and identification of the significant substance in the extract (spilanthol) were performed using Gas Chromatography (GC-FID), Thin Layer Chromatography (TLC), and Attenuated Total Reflectance Infrared Spectroscopy (FTIR-ATR). The results showed significant increases in antioxidant activity compared to the sample without extract. This positive aspect opens a perspective for using jambu flower extract as a prominent antioxidant adjunct in beer.